DIPG-38. DIANHYDROGALACTITOL (VAL-083) WITH AZD1775 INCREASES SURVIVAL IN DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG), IN VIVO. (23rd April 2019) - Steino, Anne; Yang, Xiaodong; Kline, Cassie; Brown, Dennis; Bacha, Jeff; Liu, Lei; Mueller, Sabine
Abstract: VAL-083 is a bi-functional DNA-targeting agent that crosses the blood-brain barrier and accumulates in brain tumors. VAL-083 induces interstrand crosslinks leading to DNA double-strand breaks and S/G2 cell-cycle arrest. We hypothesized that by inhibiting G2 checkpoint regulator kinase Wee1, cancer cells with VAL-083 induced DNA damage would progress past the G2 checkpoint leading to premature mitosis and cancer cell death. Herein we assess the activity of VAL-083 as well as in combination with the Wee1 inhibitor AZD1775 in patient-derived model systems of DIPG. DIPG derived cell-lines SF8628 and NEM157 (H3.3K27) were treated with increasing concentrations of single agent VAL-083 and in combination with AZD1775. To determine synergistic activity, we calculated the combination index (CI) using the Chou-Talalay method. In vivo activity of VAL-083 (3 mg/kg) as single agent or in combination with AZD1775 (60 mg/kg) was assessed in an orthotopic engraftment model of DIPG (SF8628). The IC50 of single agent VAL-083 ranged from 1µM to 10µM. The combination of VAL-083 and AZD 1775 exhibited synergistic activity in SF8628 and NEM157 with CI values ranging from 0.4 to 0.95 (CI<1 indicating synergy). In vivo, single-agent VAL-083 and in combination with AZD1775 conferred significant survival benefit compared to both untreated control and single-agent AZD1775. The median survival for mice treated with VAL-083 alone was 54.5 days vs. control (44 days, p=0.0004) and the combination was 62 days vs. control (44 days, p<0.0001) or mice treated with single-agent AZD1775 (47 days, p=0.0839). Our results suggest that VAL-083 in combination with a Wee1 inhibitor such as AZD1775 might offer a promising new therapeutic strategy for children with DIPG. Ongoing studies assessing the in vivo activity in other DIPG models as well as exploring the underlying mechanism-of-action of the combination strategy will be reported.